Asn-Gly-Arg-modified polydopamine-coated nanoparticles for dual-targeting therapy of brain glioma in rats - Hu, Jiangang (Oncotarget, 2016)
The blood-brain barrier (BBB) is the major clinical obstacle in the chemotherapeutic management of brain glioma. Here we synthesized a pH-sensitive dual-targeting doxorubicin (DOX) carrier to compromise tumor endothelial cells, enhance BBB transportation, and improve drug accumulation in glioma cells. The drug delivery system was constructed with polydopamine (PDA)-coated mesoporous silica nanoparticles (NPs, MSNs) and the PDA coating was functionalized with Asn-Gly-Arg (NGR), a ligand with specific affinity for cluster of differentiation 13 (CD13). MSN-DOX-PDA-NGR showed a higher intracellular accumulation in primary brain capillary endothelial cells (BCECs) and C6 cells and greater BBB permeability than the non-targeting NPs (MSN-DOX-PDA) did in vitro. Ex vivo and in vivo tests showed that MSN-DOX-PDA-NGR had a higher accumulation in intracranial tumorous tissue than the undecorated NPs did. Furthermore, the antiangiogenesis and antitumor efficacy of MSN-DOX-PDA-NGR were stronger than that of MSN-DOX-PDA. Therefore, these results indicate that the dual-targeting vehicles are potentially useful in brain glioma therapy.